Comparação da eficiência de reatores aeróbios com paralisações escalonadas de aeração em diferentes concentrações de matéria orgânica no tratamento de águas residuárias do processamento de farinha de mandioca - Bueno, Gisele Ferreira [UNESP] (2010)
Cassava wastewater, generated during cassava processing, is a highly polluting and toxic waste. This study aimed to assess the relationship of cassava treatment efficiency in two aerobic sequencing batch reactors, cylindrical plastics (31cm height x 9cm diameter), with 2.0 liters capacity and 1.5 liters of work volume, a ratio of diameter and height of the liquid 1:2.5, with a running time of 24 hours and stoppage aeration for 16 hours with average feed of 2,500 and 6,000 mg COD. L -1. COD, pH, SVI and F/M were analyzed. The results obtained in the two reactors showed an average reduction of 94.1% and 76.8% organic content, respectively; pH values showed a rising in the output pH values compared to entry ones; SVI values obtained: 54.1 mL/g, 99.3 mL/g, respectively in a F/M ratio values worked out of 0.4 d-1 and 1,1 d-1 , respectively. The results demonstrated that the process has generated considerable saving in energy consumption compared to traditional continuous systems, was efficient and did not affect the efficiency overly of the reactor.